(untitled) (Fiep Bulletin - online, 2016)
Adventure tourism is closely related to nature. In the case of rafting, there are aspects in which its activity can cause impacts to the environment. The equipment use and how the activity is performed directly affect the intensity of the impacts, therefore, the planning it is essential for sustainability of the sport.